A Calling of Circles: Ruminations on Living the Research in Everyday Practice - Carl Leggo (Networks: An Online Journal for Teacher Research, 2002)
I begin with a narrative of living the research in everyday practice. The story of teaching is always a tangled story. The story of teaching is a story that we can never get right because the right ways are often found only by pursuing or even stumbling in the wrong ways. Most of my students know me as a gentle and generous teacher with a constant store of words of encouragement. I relate to my students out of an abiding sense of desire to help them know their desires. My desire is to call out my students' desires. But for a long time in my teaching I wanted my students' desires to imitate and recapitulate, even fulfill, my desires. And I knew frequent frustration. Then I met a wise old woman who taught me the most important lesson I have ever learned about teaching, a lesson I continue to learn as I continue to lean on the old woman's wisdom.